KEPEMIMPINAN TRANSFORMASIONAL, MOTIVASI KERJA, DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI DI DINAS PENDIDIKAN KOTA MADIUN - Sugito, Sugito (Penerbit Lafadz Jaya, 2025)
This study aims to describe the influence of transformational leadership, work motivation, and work discipline on employee performance at the Education Office of Madiun City. Using a descriptive qualitative approach, data were collected through in-depth interviews and direct observations of key informants within the institution. The findings show that transformational leadership is applied through open communication, employee empowerment, and the provision of work inspiration. Employee motivation is enhanced through performance recognition and involvement in decision-making processes. Work discipline is reflected in adherence to work hours, timely task completion, and compliance with organizational rules. The combination of these three factors significantly contributes to improving employee performance, particularly in delivering optimal public services. These findings illustrate that the success of public organizations is strongly influenced by the quality of leadership, internal employee motivation, and a well-established work discipline culture.